let a, b, c be Real; :: thesis: ( a <> 0 & delta (a,b,c) >= 0 implies for x being Real holds
( not Polynom (a,b,c,x) = 0 or x = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or x = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) ) )

assume that
A1: a <> 0 and
A2: delta (a,b,c) >= 0 ; :: thesis: for x being Real holds
( not Polynom (a,b,c,x) = 0 or x = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or x = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) )

now :: thesis: for y being Real holds
( not Polynom (a,b,c,y) = 0 or y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) )
set e = a * c;
let y be Real; :: thesis: ( not Polynom (a,b,c,y) = 0 or y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) )
set t = ((a ^2) * (y ^2)) + ((a * b) * y);
assume Polynom (a,b,c,y) = 0 ; :: thesis: ( y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) )
then a * (((a * (y ^2)) + (b * y)) + c) = a * 0 ;
then ((a * (a * (y ^2))) + (a * (b * y))) + (a * c) = 0 ;
then A3: ((((a ^2) * (y ^2)) + ((a * b) * y)) + ((b ^2) / 4)) - ((b ^2) * (4 ")) = - ((4 * (a * c)) * (4 ")) ;
A4: delta (a,b,c) = (b ^2) - ((4 * a) * c) by QUIN_1:def 1;
A5: now :: thesis: ( ((a * y) + (b / 2)) - (sqrt (((b ^2) - (4 * (a * c))) / 4)) = 0 implies y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) )
assume ((a * y) + (b / 2)) - (sqrt (((b ^2) - (4 * (a * c))) / 4)) = 0 ; :: thesis: y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a)
then (a * y) + (b / 2) = (sqrt ((b ^2) - (4 * (a * c)))) / 2 by ;
then a * y = - ((b * (2 ")) - ((sqrt ((b ^2) - (4 * (a * c)))) * (2 ")))
.= ((- b) * (2 ")) + ((sqrt (delta (a,b,c))) * (2 ")) by A4 ;
then y = (((- b) * (2 ")) + ((sqrt (delta (a,b,c))) * (2 "))) / a by
.= (((- b) * (2 ")) + ((sqrt (delta (a,b,c))) * (2 "))) * (a ") by XCMPLX_0:def 9
.= ((- b) + (sqrt (delta (a,b,c)))) * ((2 ") * (a "))
.= ((- b) + (sqrt (delta (a,b,c)))) * ((2 * a) ") by XCMPLX_1:204 ;
hence y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) by XCMPLX_0:def 9; :: thesis: verum
end;
A6: now :: thesis: ( ((a * y) + (b / 2)) + (sqrt (((b ^2) - (4 * (a * c))) / 4)) = 0 implies y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) )
assume ((a * y) + (b / 2)) + (sqrt (((b ^2) - (4 * (a * c))) / 4)) = 0 ; :: thesis: y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a)
then (a * y) + (b / 2) = - (sqrt (((b ^2) - (4 * (a * c))) / 4)) ;
then (a * y) + (b / 2) = - ((sqrt ((b ^2) - (4 * (a * c)))) / 2) by ;
then a * y = - ((b * (2 ")) + ((sqrt ((b ^2) - (4 * (a * c)))) * (2 ")))
.= ((- b) * (2 ")) - ((sqrt (delta (a,b,c))) * (2 ")) by A4 ;
then y = (((- b) * (2 ")) - ((sqrt (delta (a,b,c))) * (2 "))) / a by
.= (((- b) * (2 ")) - ((sqrt (delta (a,b,c))) * (2 "))) * (a ") by XCMPLX_0:def 9
.= ((- b) - (sqrt (delta (a,b,c)))) * ((2 ") * (a "))
.= ((- b) - (sqrt (delta (a,b,c)))) * ((2 * a) ") by XCMPLX_1:204 ;
hence y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) by XCMPLX_0:def 9; :: thesis: verum
end;
((b ^2) - (4 * (a * c))) / 4 >= 0 / 4 by ;
then ((a * y) + (b / 2)) ^2 = (sqrt (((b ^2) - (4 * (a * c))) / 4)) ^2 by ;
then (((a * y) + (b / 2)) - (sqrt (((b ^2) - (4 * (a * c))) / 4))) * (((a * y) + (b / 2)) + (sqrt (((b ^2) - (4 * (a * c))) / 4))) = 0 ;
hence ( y = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or y = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) ) by ; :: thesis: verum
end;
hence for x being Real holds
( not Polynom (a,b,c,x) = 0 or x = ((- b) + (sqrt (delta (a,b,c)))) / (2 * a) or x = ((- b) - (sqrt (delta (a,b,c)))) / (2 * a) ) ; :: thesis: verum